Membangun Argumentasi Prinsip-Prinsip Moderasi Beragama Dalam Perspektif Al-Quran - Muqit, Abd. (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2023)
The current radicalism and extremism became the background for the initiation of the theory of religious moderation. In the Indonesian context, religious moderation is highly emphasized and has even become a program apart from the Ministry of Religion of the Republic of Indonesia. Along with these developments, the author is interested in studying religious moderation in interpreting the Koran using thematic methods. The results of the research concluded that the Koran aims to do good to each other among fellow believers and act fairly towards them, build friendships, respect other people's religions, not incite other religions, and carry out the teachings of their respective religions and religions and not disturb them. These things can be used as principles that must be applied in building religious moderation in Indonesia.